Why Does SARS-CoV-2 Infection Induce Autoantibody Production? - Macela, Ales; Kubelkova, Klara (Pathogens (Basel, Switzerland), 2021)
SARS-CoV-2 infection induces the production of autoantibodies, which is significantly associated with complications during hospitalization and a more severe prognosis in COVID-19 patients. Such a response of the patient's immune system may reflect (1) the dysregulation of the immune response or (2) it may be an attempt to regulate itself in situations where the non-infectious self poses a greater threat than the infectious non-self. Of significance may be the primary virus-host cell interaction where the surface-bound ACE2 ectoenzyme plays a critical role. Here, we present a brief analysis of recent findings concerning the immune recognition of SARS-CoV-2, which, we believe, favors the second possibility as the underlying reason for the production of autoantibodies during COVID-19.
Keywords: innate immune recognition; COVID-19; SARS-CoV-2; autoantibodies; ACE2 signaling